Spam Reviews Detection Using Hadoop (International Journal of Engineering and Computer Science, 2017)
Product reviews are now widely used by individuals and organizations for their decision making. However, due to the reason of profit or fame, people try to manipulate the system by opinion spamming (e.g., writing spam reviews) to promote or demote some target products. For reviews to reflect genuine user experiences and opinions, such spam reviews should be detected. The project elaborated below aims at filtering the spam reviews, by providing an effective method. Usage of MapReduce technique provided by Apache Hadoop is highly emphasized for processing reviews. In this paper, the technique used for the same is described which substantially reduces time complexity when implemented.